Peningkatan Penguasaan Konsep Siswa Kelas XI IPA pada Materi Suhu dan Kalor melalui Modeling Instruction - Daniar Pangastiningasih Etikamurni; Sutopo Sutopo (Pascasarjana Universitas Negeri Malang, 2019)
Abstract: This research was aimed to determine the magnitude of the increase in student's conceptual understanding through modeling instruction on temperature and heat material. The subjects of this study were students of SMAN 2 Batu in XI grade which amounted to 65 students. The research design used one group pretest - posttest design which was analyzed quantitatively. Data obtained from the pretest and posttest values are then presented in percentage and statistics. Data was presented through calculation of the average number of students in each indicator, then it was calculated statistically by using the Kolmogorov - Sminorv as normality test, Wilcoxon signed rank for difference test, then followed by N-gain test and effect size to determine the magnitude of increase and influence on variables. The results showed that there was an increase of 0.24 (low category) at the posttest value of students after modeling instruction in the class. The magnitude of the influence of modeling instruction on increasing student's conceptual understanding is equal to 0.69 which falls into the sufficient category. Abstrak: Penelitian ini bertujuan untuk mengetahui besarnya peningkatan penguasaan konsep siswa melalui modeling instruction pada materi suhu dan kalor. Subjek penelitian ini adalah para siswa SMAN 2 Batu kelas XI yang berjumlah 65 siswa. Design penelitian menggunakan one group pretest - posttest design yang dianalisis secara kuantitatif. Data diperoleh dari nilai pretest dan posttest yang kemudian disajikan dalam bentuk persentase dan statistik. Penyajian data dalam bentuk persentase didapatkan melalui perhitungan rata-rata jumlah siswa pada tiap indikator soal dan penyajian data dalam bentuk statistik diperoleh melalui beberapa pengujian, seperti uji normalitas Kolmogorov - Sminorv, uji beda Wilcoxon signed rank, kemudian dilanjutkan uji N-gain dan effect size untuk mengetahui besarnya peningkatan dan pengaruh terhadap variabel. Hasil penelitian menunjukkan bahwa ada peningkatan sebesar 0.24 (kategori rendah) pada nilai posttest siswa setelah dilakukan modeling instruction di kelas. Besarnya pengaruh modeling instruction terhadap peningkatan penguasan konsep siswa adalah sebesar 0.69 yang masuk ke dalam kategori cukup.